Audience Education, Concert Pedagogy – Hans Krása’s Children’s Opera: Brundibár (Training and Practice : Journal of Educational Sciences, 2017)
The objective of a symphony orchestra’s musical education programme is to establish accurate and long term experience in schoolchildren and young people, which encourages them to appreciate classical music later in life. Such a programme leads students into the world of instruments and music, provides an enjoyable and at the same time useful extension to regular music classes. Brundibár, an extremely touching and tragic children’s opera by Hans Krása, has played a special role in the children’s opera series of the Budapest Festival Orchestra’s (BFO) educational program. This essay is evoking the origins of the opera, the circumstances of the first performances in Theresienstadt, and the recent performances by BFO.